Potential activity of Traditional Chinese Medicine against Ulcerative colitis: A review - Liu, Yang; Li, Bao-Guo; Su, Yu-Hua; Zhao, Ruo-Xi; Song, Peng; Li, Hui; Cui, Xin-Hai; Gao, Hong-Mei; Zhai, Run-Xiang; Fu, Xian-Jun; Ren, Xia (Journal of ethnopharmacology, 2022)
Plant materials are used as complementary and alternative therapies all over the world for the treatment of various diseases. Ulcerative colitis (UC), a chronic nonspecific inflammatory bowel disease listed as one of the modern refractory diseases by the World Health Organization, has a long course, is challenging to cure, and is prone to cause cancer. Recent years have witnessed a growing trend of applying traditional Chinese medicine (TCM) to UC. This review presents an overview of the pathogenesis of UC and reports the therapeutic effect of TCM on UC (including TCM prescriptions, single TCM, and treatments using TCM ingredients) to provide a theoretical basis for the use of TCM in treating UC. We performed a collection and collation of relevant scientific articles from different scientific databases regarding TCM and its usefulness in treating UC. In this paper, the therapeutic effect of TCM is summarized and analyzed according to the existing experimental and clinical research. There are positive signs that TCM primarily regulates inflammatory cytokines, intestinal flora, and the immune system, and also protects the intestinal mucosa. Hence, it can play a role in treating UC. TCM has a definite curative effect in the treatment of UC. It can alleviate and treat UC in a variety of ways. We should take syndrome differentiation and treatment differentiation as the basis. With the help of modern medicine, TCM's clinical curative effects can be enhanced for the treatment of UC. [Display omitted]